The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5539/ijef.v9n9p182
|View full text |Cite
|
Sign up to set email alerts
|

Nexuses between Economic Factors and Stock Returns in China

Abstract: Economist and stock managers always focus on stock market return. This study investigated short and long run relationship between economic factors and stock returns in China by applying ARDL approach from 01/2000 to 12/2016. Estimated results of bound test for co-integration shows that long run relationships exist among the variables except inflation rate. Results of short and long run ARDL demonstrate that exchange rate and inflation rate have positive effect on stock returns in China while interest rate have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
6
13
0
4
Order By: Relevance
“…Previous studies by Khan et al, (2017); (Kandir, 2008); (Bilson et al, 2001); (Tsoukalas, 2003) showed exchange rate has significant effect on stock return. Some of the companies listed on the Indonesia Stock Exchange (IDX) have substantial foreign debt.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies by Khan et al, (2017); (Kandir, 2008); (Bilson et al, 2001); (Tsoukalas, 2003) showed exchange rate has significant effect on stock return. Some of the companies listed on the Indonesia Stock Exchange (IDX) have substantial foreign debt.…”
Section: Introductionmentioning
confidence: 90%
“…Kandir (2008) and Rjoub et al, (2009) found a significant relationship between the stock return and unanticipated inflation in Turkey. Khan et al, (2017) found the exchange rate and inflation rate have a positive effect on stock return in China. Flannery and Protopapadakis (2002) found stock market returns are significantly correlated with inflation on NYSE, AMEX, and NASDAQ stock market.…”
Section: Introductionmentioning
confidence: 99%
“…The used datasets were composed in a legitimate manner, completely obeying with the terms of service of the both sources. By following Qaio et al [46]; Botta et al [47]; Ranco et al [48]; Khan et al [49] and Yun and Yoon [50] returns of both variables are calculated by taking the natural logarithm difference of stock returns of Shanghai stock exchange composite index and the (WTI) oil prices returns, as shown in the following Equations. Where SSERM and OilpM are the returns of Shanghai stock exchange composite index and the oil prices (WTI) returns respectively, SSERM t and OilpM t are the today prices and SSERM t −1 , OilpM t −1 are the previous day prices.…”
Section: Methodsmentioning
confidence: 99%
“…Following previous researchers Youssef (2015a, 2015b), Youssef (2015a, 2015b) and Alshehry and Belloumi (2015) and Khan et al (2017Khan et al ( , 2019a) in this study we use the bound testing approach proposed by Pesaran et al (2001) to estimate the long run estimates between CO 2 emission, economic growth, energy consumption. Prior studies in energy economics suggest several econometric approaches to check the existence of the cointegration.…”
Section: Autoregressive Distributive Lagmentioning
confidence: 99%